2021
DOI: 10.1111/jfpp.15492
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of specific volatile components in braised pork with different tastes by SPME‐GC/MS and electronic nose

Abstract: Braised pork is a meat product that is prepared with pork belly, soy sauce, and other ingredients. Such a product is originated in China but popular around the world. There are many preparations to meet different demands. For instance, people prefer sweet braised pork by adding a large amount of brown sugar and black vinegar in eastern China, while spicy braised pork is preferred in middle China and salty taste is preferable in northern China (Wang, 2017). In addition, preparation methods may vary greatly to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Amyl alcohol, 1-octen-3-ol, and furan-2-ylmethanol have low olfactory thresholds and have been demonstrated to be key volatile compounds in the aroma studies of fish sauce, brown sugar, pork, Peking duck, etc. [ 9 , 43 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amyl alcohol, 1-octen-3-ol, and furan-2-ylmethanol have low olfactory thresholds and have been demonstrated to be key volatile compounds in the aroma studies of fish sauce, brown sugar, pork, Peking duck, etc. [ 9 , 43 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the field of VOC detection, E-nose combined with GC-MS is the most commonly used detection method. For example, disease surveillance (Thriumani et al, 2018), air quality (Moufid et al, 2021), herbal medicine (Long et al, 2019), food fermentation (Dai et al, 2018), meat (Da et al, 2021), fish , fungi and oomycetes (Loulier et al, 2020), and so on.…”
Section: Nondestructive Detection Methodsmentioning
confidence: 99%
“…Such a difference was in accordance with the results of sensory evaluation. In previous studies, E-nose sensor signals were shown to have a certain correlation with sensory attributes [48,49].…”
Section: Sensory Evaluationmentioning
confidence: 95%